PENERAPAN METODE KEPELATIHAN CABANG OLAHRAGA PERMAINAN DI SURAKARTA - Umar, Fadilah (Pendidikan Dan Kepelatihan Olahraga, 2010)
This research has the objective to determine: (1) Application of the method is training at sports clubs play in Surakarta in 2009. (2) Preparation of training programs in sports clubs play in Surakarta in 2009. The research method used is descriptive research method degan way surveys. The sample used was of trainers at sports clubs play in the city of Surakarta. Sample making techniques with random sampling. Total sample with 57 trainers from eight (8) sports such as football game, volleyball, basketball, futsal, tennis, table tennis, softball, baseball, and badminton. Research instrument uses a questionnaire with dichotomous response pattern (yes, no) with a score for each answer (yes) is given a score of